Effect of vildagliptin compared to glimepiride on postprandial proinsulin processing in the β cell of patients with type 2 diabetes mellitus. Issue 6 (6th February 2013) - Forst, T.; Dworak, M.; Berndt‐Zipfel, C.; Löffler, A.; Klamp, I.; Mitry, M.; Pfützner, A.
<x xml:space="preserve">Abstract</x> This study compared the effect of Glimepiride versus Vildagliptin on β‐cell function and the release of intact proinsulin (PI) in patients with type 2 diabetes mellitus. Patients on metformin monotherapy were randomized to add on treatment with Vildagliptin or Glimepiride. A standardized test meal was given at baseline, after 12 and 24 weeks of treatment. Insulin, PI and blood glucose values were measured in the fasting state and postprandial for 300 min. Fasting PI levels significantly decreased in the Vildagliptin group. The area under the curve for the postprandial release of PI decreased during Vildagliptin and increased during Glimepiride treatment. The proinsulin to insulin ratio declined in the Vildagliptin group, whereas it did not change significantly in the Glimepiride group. Addition of Vildagliptin to ongoing Metformin treatment reconstitutes the disproportionality of the proinsulin to insulin secretion from the β cell.